Kepribadian dan Motivasi Kerja Mempengaruhi Komitmen Normatif - Hegar Harini; Adisel Adisel (Alignment:Journal of Administration and Educational Management, 2020)
The purpose of this study was to determine the personality and work motivation to influence the normative commitment of the principal. This study used a survey method involving 90 school principals from public high schools in DKI Jakarta. The data obtained were analyzed using the path analysis approach. In conclusion, personality and work motivation have a positive direct effect on normative commitment of school principals. This indicates that the better the personality and the higher the work motivation, the higher the normative commitment of the school principal. Keywords: Personality, Motivation, Normative Commitment.